2009
DOI: 10.1021/ja907967y
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Monoester Hydrolysis in Cyclohexane

Abstract: The hydrolysis of simple phosphate monoesters is among the most difficult reactions that are subject to catalysis by enzymes, and it has been suggested that extraction of the substrates from solvent water may contribute to the catalytic effects of phosphohydrolases. Here, we show that the tetrabutylammonium salt of neopentyl phosphate enters wet cyclohexane at concentrations sufficient to allow determination of its rate of hydrolysis. The second-order rate constant for hydrolysis of the phosphomonoester dianio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The k cat value of 570 s Ϫ1 measured for PPase at 25°C in this work is slightly larger than a literature value of 290 s Ϫ1 (18). PP i Hydrolysis in DMSO-Because transfer of the substrate from bulk water to nonpolar solvents greatly accelerates the second-order rate constant for hydrolysis of phosphate monoesters and diesters (27,28), we sought to determine whether desolvation might also increase the rate of PP i hydrolysis. PPase has an unusually polar active site (10), so we chose to model PP i desolvation in the active site of PPase by transferring PP i from bulk water to a polar aprotic solvent, DMSO.…”
Section: Spontaneous Hydrolysis Of Pp Imentioning
confidence: 56%
“…The k cat value of 570 s Ϫ1 measured for PPase at 25°C in this work is slightly larger than a literature value of 290 s Ϫ1 (18). PP i Hydrolysis in DMSO-Because transfer of the substrate from bulk water to nonpolar solvents greatly accelerates the second-order rate constant for hydrolysis of phosphate monoesters and diesters (27,28), we sought to determine whether desolvation might also increase the rate of PP i hydrolysis. PPase has an unusually polar active site (10), so we chose to model PP i desolvation in the active site of PPase by transferring PP i from bulk water to a polar aprotic solvent, DMSO.…”
Section: Spontaneous Hydrolysis Of Pp Imentioning
confidence: 56%
“…The above preference for the stepwise mechanism may be relevant for the experimental observation [5,6] that the rate of hydrolysis is significantly enhanced in low dielectric media. For example, Stockbridge and Wolfenden [5] demonstrated that the hydrolysis of neopentyl phosphate dianion ðNP 2À Þ proceeds orders of magnitude faster in wet cyclohexane than in aqueous solution. This rate enhancement corresponds to a decrease in activation free energy by 11-12 kcal/mol [5].…”
Section: Resultsmentioning
confidence: 88%
“…For example, Stockbridge and Wolfenden [5] demonstrated that the hydrolysis of neopentyl phosphate dianion ðNP 2À Þ proceeds orders of magnitude faster in wet cyclohexane than in aqueous solution. This rate enhancement corresponds to a decrease in activation free energy by 11-12 kcal/mol [5]. The above rate enhancement is consistent qualitatively with the dramatic decrease in free energy barrier shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations